59.4k views
4 votes
7. −4(2z+6)−12=4

8. 3/2(x−2)−5=19




As you could see i'm not really good with math

User Sarson
by
5.7k points

2 Answers

5 votes

7)

-4(2z + 6) - 12 = 4

-4(2z) + -4(6) -12 = 4 distributed -4 into (2z + 6)

-8z - 24 - 12 = 4 simplified the multiplied terms

-8z - 36 = 4 added like terms (-24 and -12)

-8z = 40 added 36 to both sides of the equation

z = -5 divided both sides by -8

Answer: z = -5

8)


(3)/(2)(x - 2) - 5 = 19


(3)/(2)(x - 2) = 24 added 5 to both sides

(x - 2) = 24(
(2)/(3)) multiplied both sides by
(2)/(3)

x - 2 = 16 simplified the multiplied term on the right

x = 18 added 2 to both sides

Answer: x = 18


User Ryan Matthews
by
5.5k points
3 votes

Hey there! :)

7. -4(2z + 6) - 12 = 4

Simplify.

-8z - 24 - 12 = 4

Simplify.

-8z - 36 = 4

Add 36 to both sides.

-8z - 36 + 36 = 4 + 36

Simplify.

-8z = 40

Divide both sides by -8.

z = -5

8. 3/2(x - 2) - 5 = 19

Simplify.

3/2x - 3 - 5 = 19

Simplify.

3/2x - 8 = 19

Add 8 to both side.

3/2x = 19 + 8

Simplify.

3/2x = 27

Multiply both sides by 2.

3/2x · 2 = 27 · 2

Simplify.

3x = 54

Divide both sides by 3.

x = 18

~hope I helped~

User Brad Rydzewski
by
6.3k points